Effects of customer relationship management on organizational performance - Ivana Nedeljković; Dejana Zlatanović; Veljko Marinković (Economic Themes, 2022)
Customer Relationship Management (CRM) is a process that focuses on initiating, maintaining, and retention of long-term customer relationships with the help of information technology, to achieve better economic performance. Therefore, the paper examines the effects of CRM dimensions on financial and marketing performance, and moderates the role of an image on these relationships. The analysis included 106 organizations on the territory of the Republic of Serbia. The paper uses descriptive statistical analysis, correlation analysis, multiple regression analysis, and moderation regression analysis. The obtained results show that there is a negative statistically significant impact of CRM technology on financial and marketing performance. On the other hand, the existence of a positive statistically significant impact of consumer knowledge management on financial and marketing performance was found, as well as the fact that the image has negative moderating effects on these two relationships. The contribution of this paper is reflected in the unique structure of the research model, in the multidimensional observation of CRM, and measuring the impact of CRM dimensions on financial and marketing performance. Given that previous research has focused more on testing the main effects, rather than the interaction effects, the originality of the work is also contributed by testing the moderator role of the image on the relationship between CRM dimensions and organizational performance.
Keywords: M30; M31; M39; 330; CRM; consumer focus; CRM organization; CRM technology; knowledge management; organizational performance; image